2020
DOI: 10.1088/1757-899x/946/1/012001
|View full text |Cite
|
Sign up to set email alerts
|

Prerequisites for the analysis of the neural networks functioning in terms of projective geometry

Abstract: It is shown that during training an artificial neural network built on elements with a threshold activation function, the weighting coefficients of each neuron can be selected from a certain discrete set, the nature of which depends on the number of neurons inputs. An example of a neuron with three inputs is considered in detail. It is shown that there are only 8 non-trivial combinations of weight coefficients that specify the work of neurons of this variety: any other combination of weight coefficients that d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…However, precisely the considerations of a philosophical nature force us to use an interpretation that based on the neural network model of the noosphere. Moreover, at present there are prerequisites for deciphering the code of neural networks [23,24]; in the future, this will make it possible to reveal those codes that are inherent in the global communication network -the noosphere.…”
Section: Discussionmentioning
confidence: 99%
“…However, precisely the considerations of a philosophical nature force us to use an interpretation that based on the neural network model of the noosphere. Moreover, at present there are prerequisites for deciphering the code of neural networks [23,24]; in the future, this will make it possible to reveal those codes that are inherent in the global communication network -the noosphere.…”
Section: Discussionmentioning
confidence: 99%
“…Since 𝑒 𝑖 are mutually canceling idempotent elements. Expression (21) unambiguously shows that the result of calculating the product of the "higher" digits really does not completely depend on the result of calculating the product of the "lower" digits.…”
Section: Number Systems With a Hybrid Base As The Basis Of The Partia...mentioning
confidence: 98%
“…It is appropriate to emphasize that for decrypting algorithms according to which trained neural networks function, multivalued logic is also of interest [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers in [12]- [14] it was shown that there is a very close relationship between the theory of error-correcting coding and the theory of neural networks, which are also often used for digital signal processing [15], [16]. This creates quite definite prospects for the practical use of multivalued logics, which are actively being developed at the present time [17], [18].…”
Section: Introductionmentioning
confidence: 99%